2009
DOI: 10.1007/s10800-009-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel IrO2 electrode with iridium–titanium oxide interlayers from a mixture of TiN nanoparticle and H2IrCl6 solution

Abstract: A novel IrO 2 anode on titanium substrate with iridium-titanium oxide interlayer (Ti/IrO x -TiO 2 /IrO 2 ) was prepared and investigated for oxygen evolution. IrO x -TiO 2 interlayer was coated on titanium substrate by impregnation-thermal decomposition method from a mixture of TiN nanoparticles and H 2 IrCl 6 solution at 500°C. The results showed that the service life of Ti/IrO x -TiO 2 /IrO 2 was a factor of six times longer than that of Ti/IrO 2 , which was attributed to the IrO x -TiO 2 interlayer, it coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
(30 reference statements)
0
7
0
2
Order By: Relevance
“…The extent of the delamination of the baseline Ti/IrO 2 electrode was more severe than that of the Ti/IrO x ‐TiO 2 /IrO 2 , with the latter lasting 420 h more at 3 A cm −2 in a 4 m H 2 SO 4 solution at 30 °C. SEM confirmed that delamination was not as pronounced for the interlayer electrode, as shown by the relative sizes of the delaminated and catalyst‐free spots supposedly lost during the ALT process (up to 50 μm × 50 μm versus 500 μm × 600 μm for the interlayer sample and reference case, respectively) …”
Section: Following Degradation By Materials Characterization and In S...mentioning
confidence: 70%
“…The extent of the delamination of the baseline Ti/IrO 2 electrode was more severe than that of the Ti/IrO x ‐TiO 2 /IrO 2 , with the latter lasting 420 h more at 3 A cm −2 in a 4 m H 2 SO 4 solution at 30 °C. SEM confirmed that delamination was not as pronounced for the interlayer electrode, as shown by the relative sizes of the delaminated and catalyst‐free spots supposedly lost during the ALT process (up to 50 μm × 50 μm versus 500 μm × 600 μm for the interlayer sample and reference case, respectively) …”
Section: Following Degradation By Materials Characterization and In S...mentioning
confidence: 70%
“…Die Ti/IrO 2 ‐Vergleichselektrode zeigte stärkere Delaminierung als das Ti/IrO x ‐TiO 2 /IrO 2 , und dieses hielt in einer 4 m H 2 SO 4 ‐Lösung bei 30 °C und 3 A cm −2 auch 420 h länger. Die SEM bestätigte eine weniger ausgeprägte Delaminierung bei der Zwischenschichtelektrode, erkennbar an der relativen Größe delaminierter sowie katalysatorfreier Stellen, die vermutlich während des ALT‐Prozesses entstanden sind (bis zu 50 μm × 50 μm für die Zwischenschichtprobe gegenüber 500 μm × 600 μm in der Referenzprobe) …”
Section: Beobachtung Der Degradation Durch Materialcharakterisierung ...unclassified
“…In general, iridium oxide has been widely preferred as a coating material for pH sensors due to its stability against dissolution, potential, chemical stability over a wide range of temperatures (up to 250 o C), fast response, low sensitivity towards ions or redox interferences, and wide pH response range (Marzouk et al, 1998;Xu et al, 2010). Because of these benefits, iridium oxide coated metal-based pH electrodes have been investigated for various applications, such as Severinghaus-type CO2 sensors for oil and gas applications; micro-environmental studies; microsystems for cell culture; and biomedical applications Ges et al, 2007;Johnson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%